MARKET CONCENTRATION DAN BANK PERFORMANCE: BUKTI EMPIRIS DARI PERBANKAN KONVENSIONAL DI INDONESIA - Garnis Irawanti; Vitasari Kusnaningrum; Koko Safitri (Media Bina Ilmiah, 2024)
This study aims to analyze the effect of market concentration and asset growth on the financial performance of conventional banking in Indonesia listed on the Indonesia Stock Exchange (IDX) during the period 2020-2023. Market concentration refers to the extent to which the banking market is dominated by a small number of large banks. This study uses secondary data from the financial statements of conventional banks listed on the Indonesia Stock Exchange (IDX) during the period 2020-2023. A sample of 11 conventional banks that meet the criteria. The data analysis technique used is multiple linear regression analysis to test the research hypothesis. The results of the study indicate that market concentration and asset growth have a significant effect on banking financial performance. High market concentration can have a positive or negative impact on financial performance, depending on the competitive conditions and operational efficiency of the bank. Meanwhile, stable asset growth tends to strengthen the financial performance of banks by increasing operational scale and efficiency. These findings provide important insights for banking management and policy makers in formulating effective strategies to improve financial performance in a competitive market environment.